HUBUNGAN KEKUATAN CORE STABILITY DENGAN FLEKSIBILITAS LOWER LIMB PADA LANSIA DI PANTI WERDHA BUDI MULIA 3 JAKARTA - Eko Prabowo; Putri Laila Syahlaa (Jurnal Ilmiah Fisioterapi, 2023)
Old age is often associated with an age that is no longer productive, it is even said to be a burden for those of productive age. These changes will affect balance, flexibility and strength in posture. Core stability is an important aspect ofposture. Flexibility can be defined as the ability to move freely and comfortably within the maximum expected range of motion. The purpose of this study was to determine the relationship between core stability strength and lower limb flexibility in the elderly. This study uses a descriptive correlation research with a cross sectional model. The measuringinstrument used in this study is flexibility using the Chair Sit and Reach Test and for core stability using the Sit Up Test, and a large sample of 31 elderly people in the Budi Mulia nursing home. The data analysis used is univariate and bivariate analysis. The results of research that has been carried out using the Spearman Rho correlation test method can be concluded that there is no relationship between core stability strength and lower limb flexibility in the elderly. The conclusion is suggested with a larger sample size and a more precise research screening, to be able to find the characteristics of a wider range of respondents which is expected to be wider.